Relationship between soil properties and forests carbon: Case of three community forests from Far Western Nepal - Pandey, H. P.; Pandey, P.; Pokhrel, S.; Mandal, R. A. (Banko Janakari, 2019)
The study was carried out in three community-managed forests of Dadeldhura district located in Far West of Nepal in 2015. The objectives of the study were to analyze biomass and soil organic carbon (SOC) accumulation and observe how primary soil nutrients and other soil properties affect the biomass and SOC in these forests. Simple random sampling method was used with 0. 62% sampling intensity. Concentric circular sample plot of various sizes were laid out for the necessary data collection. ANOVA, Tukey’s HSD and correlation tests were performed. The carbon density differed significantly (p<0. 05) in the studied CFs. The Tukey’s test showed the BPCF had significantly higher (p<0. 05) carbon density than other CFs. The correlation between biomass density (t/ha) and soil bulk density was very weak and it was not significant. However, biomass density revealed significant (p<0.05) negative correlation with SOC(r = -0.38) and Phosphorous (r = -0.56) content in the soil. Biomass density had no significant correlation with rest of the parameters. Similarly, SOC had significant (p<0.05) positive correlation with all the parameters except with soil bulk density (p<0.05, r= -0. 88). Despite the higher biomass in forests, we found the lesser amount of SOC and primary soil nutrients in the soil. Similarly, acidic soils with higher contents of primary soil nutrients (NPK) had relatively higher SOC whereas higher bulk density decreased the SOC content. Results revealed that community-managed forests seemed a viable source of biomass production and carbon sink to combat the global environmental problem (global warming). These types of forests have conserved relatively the higher biomass (biomass carbon) than normally (business-as-usual )managed forests. This output would be a reference to the policy maker, national and international communities of diverse fields who are engaged in forest carbon services related activities such as reducing emission from deforestation and forest degradation(REDD), clean development mechanism (CDM) and forest management in terms of production. Similar studies are recommended in larger geographical areas and different ecological zones to generalize the inference.